Dampak Nilai Tekanan Menggunakan Metode Standar Terhadap Daya Dukung Tanah Dasar (subgrade) - Miranti, Yesi; Setyanto, Setyanto; Sulistyorini, Rahayu (Universitas Lampung, 2020)
The subgrade is a very important role in road construction because it is the beginning of determining the quality and capacity of the soil bearing capacity. One way to strengthen the soil is by soil compaction because it can reduce the amount of unwanted soil subsidence and to rearrange the soil grain structure, so that it becomes denser so that the soil will be denser.This study used grained soil, the type of silty sand from Muara Dua Village, Ulu Belu District, Tanggamus Regency, Lampung Province. The method used is standard compaction and laboratory CBR to determine the impact of the pressure value using a modified press device. The burden used in this research is 3 MPa, 6 MPa, 9 MPa, 12 MPa, and 15 MPa.In the modified press tool test, the values obtained were 12.1 MPa and Laboratory CBR for 3 MPa pressure was 2.7%, 6 MPa pressure was 3%, 9 MPa pressure was 7.8%, 12 MPa pressure was 12.3%, and pressure 15 Mpa of 15.9%. So it can be concluded from the impact of the pressure value using a modified press tool is that the greater the pressure value, the CBR value will increase.Keywords: Standar Proctor, CBR Laboratory, Modification Press Tool.